2007
DOI: 10.1203/pdr.0b013e3180674dc6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hyperoxia on the Neonatal and Adult Developing Dendritic Cell

Abstract: ABSTRACT:Oxygen is essential therapy for neonates with acute respiratory failure, including those with infections. However, high oxygen levels may be counterproductive for overcoming infections because hyperoxia may kill cells, including dendritic cells that are essential to the emergence of the pulmonary immune system and pivotal in mounting immune responses to infections. We studied the impact of hyperoxia on developing dendritic cells from neonatal cord blood and adult blood monocytes, comparing viability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Exposure to hyperoxia caused a decrease in viability when we grouped all cells. Masalunga et al describe an increase in necroptosis and apoptosis in progenitor cells treated with chronic elevated oxygen levels [Masalunga et al, 2007]. Analogous to our study, Aly et al , found comparable viability rates of MSCs isolated from preterm and term cord cells under normal culture conditions [Aly et al, 2012].…”
Section: Discussionsupporting
confidence: 88%
“…Exposure to hyperoxia caused a decrease in viability when we grouped all cells. Masalunga et al describe an increase in necroptosis and apoptosis in progenitor cells treated with chronic elevated oxygen levels [Masalunga et al, 2007]. Analogous to our study, Aly et al , found comparable viability rates of MSCs isolated from preterm and term cord cells under normal culture conditions [Aly et al, 2012].…”
Section: Discussionsupporting
confidence: 88%
“…ROS could damage cells, tissues, and the entire organism. Prolonged exposure to high levels of oxygen generates excessive ROS, induces oxidative stress responses, affects immune response and DNA integrity, and causes cell death (Webster et al., ; Mantell and Lee, ; Lee and Choi, ; Tandara and Mustoe, ; Barker et al., ; Bhandari et al., ; Masalunga et al., ; Ogawa et al., ). The production of ROS has not been measured in the present study, however, abruptly changed oxygen availability may increase ROS production, as reflected by changes in mitochondrial function, and therefore, affects lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged exposure to high oxygen generates excessive reactive oxygen species, induces cell death and oxidative stress responses, affects immune response and DNA integrity and modulates cell growth [4], [5], [6], [7], [8]. Disorders including neurodegenerative and chronic inflammatory diseases, as well as damage from ischemia and consequent reperfusion to the heart, lung, retina, brain, and other organs result, by and large, from oxidant injury.…”
Section: Introductionmentioning
confidence: 99%